Conduct risk: towards a model for assessment and remediation. (15th May 2018) - Daly, Mary; Butler, Tom
Abstract: Widespread misconduct in Financial Services organisations prior to and since 2008 has put organisational culture centre stage in the minds of regulators. There is no one definition of Conduct Risk across the regulatory requirements for Financial Services organisations. This paper presents a research in progress development that provides the various groups and stakeholders in an organisation with a shared conceptualisation of what conduct culture is, along with a common language to communicate canonical accepted behaviours. The paper also describes an evaluation and diagnostic tool for organisations which has two primary components (1) a Conduct Risk Model (CRM) and (2) the Conduct Risk Diagnostic System (CRDS). The CRM is designed to comprehensively capture each of the primary domains of conduct risk in a detailed taxonomy and ontology. The CRDS diagnostics are designed to assess, measure and supervise the conduct risk areas and domains and to provide decisional guidance.